Promoting Inclusion and Well-Being Through Inclusive Physical Education and Parasports: an Approach for Adolescents with Motor Impairment - Omar Ben Rakaa; Mustapha Bassiri; Said Lotfi (Physical Education Theory and Methodology)
Objectives. This study aimed to examine the impact of inclusion students with motor impairment (MI) into adapted physical education (APE) and school para-athletics on their feeling of pedagogical and school inclusion, as well as on their psychological well-being and self-esteem.